Evaluation of Mimusops elengi L. flowers using pharmacognostic approach - Shailajan, Sunita; Gurjar, Deepti (Pharmacognosy Communications)
Mimusops elengi L. (Sapotaceae, Bakul) is an integral part of many Ayurvedic formulations. Flowers of M. elengi have been traditionally used for their therapeutic activities like antiulcer, wound healing, antioxidant, etc. Flowers are also reported as a brain tonic, expectorant and have been used for the treatment of asthma. Materials and methods: The present study was aimed to evaluate the pharmacognostic profile of M. elengi flowers as per the standard methods which included evaluation of proximate characters, heavy metals and chromatographic characterization. The study also included evaluation of safety profile of the plant in Albino Wistar rats as per the OECD test guidelines no. 420. Results: Various analytical values for M. elengi flowers were established. M. elengi flowers were found to be a source of terpenoids and phenolics as per the results of chromatographic characterization. M. elengi flowers were also found safe up to an oral dose of 2.0 g/kg body weight in rats. Conclusion: The pharmacognostic profile for M. elengi flowers obtained as a finding of this research work will contribute in their identification and standardization.
Keywords: Mimusops elengi L. flowers; physicochemical evaluation; phytochemical evaluation; safety evaluation